Government Responsibility to Protect People’s Rights Over the Clean Water - Muhammad Nadzir (Hang Tuah Law Journal, 2017)
Water plays a very important role in supporting human life and other living beings as goods that meet public needs. Water is one of the declared goods controlled by the state as mentioned in the constitution of the republic of Indonesia. The state control over water indicated that water management can bring justice and prosperity for all Indonesian people. However, in fact, water currently becomes a product commercialized by individuals and corporations. It raised a question on how the government responsibility to protect the people's right to clean water. This study found that in normative context, the government had been responsible in protecting the people‟s right over the clean water. However, in practical context, it found that the government had not fully protected people's right over clean water. The government still interpreted the state control over water in the form of creating policies, establishing a set of regulations, conducting management, and also supervision.